Preclinical Studies of Chiauranib Show It Inhibits Transformed Follicular Lymphoma through the VEGFR2/ERK/STAT3 Signaling Pathway - Yuanfang Tang; Mengya Zhong; Guangchao Pan; Jinshui Tan; Chendi Xie; Yuelong Jiang; Jingwei Yao; Weihang Shan; Jiaqi Lin; Jiewen Huang; Yating Liu; Zhifeng Li; et al. (MDPI AG, 2022)
Transformed follicular lymphoma (t-FL), for which there is no efficient treatment strategy, has a rapid progression, treatment resistance, and poor prognosis, which are the main reasons for FL treatment failure. In this study, we identified a promising therapeutic approach with chiauranib, a novel orally developed multitarget inhibitor targeting VEGFR/Aurora B/CSF-1R. We first determined the cytotoxicity of chiauranib in t-FL cell lines through CCK-8, EdU staining, flow cytometry, and transwell assays. We also determined the killing effect of chiauranib in a xenograft model. More importantly, we identified the underlying mechanism of chiauranib in t-FL tumorigenesis by immunofluorescence and Western blotting. Treatment with chiauranib significantly inhibited cell growth and migration, promoted apoptosis, induced cell cycle arrest in G2/M phase, and resulted in significant killing in vivo. Mechanistically, chiauranib suppresses the phosphorylation level of VEGFR2, which has an anti-t-FL effect by inhibiting the downstream MEK/ERK/STAT3 signaling cascade. In conclusion, chiauranib may be a potential therapy to treat t-FL, since it inhibits tumor growth and migration and induces apoptosis by altering the VEGFR2/ERK/STAT3 signaling pathway.